The Nowhere Stone: Unusually Located Intrahepatic Calculi in a Patient with Low Phospholipid-associated Cholelithiasis Syndrome - Suresh, Indrajit; Lokesh, E.; Suhas, C.; Nanaiah, Amrit (Journal of Digestive Endoscopy, 2019)
Intrahepatic calculi or hepatolithiasis is an uncommon phenomenon which is found in relatively higher rates in eastern Asian countries. Patients usually present with features of cholangitis or intrahepatic abscess and are at risk for developing cholangiocarcinoma. Correct diagnosis and management often pose challenges. A 42-year-old female presented with a history of episodic upper abdominal pain since 8 years. Initial imaging studies showed evidence of biliary calculi, but were confounding in their localization. Magnetic resonance cholangiopancreatography showed two large calculi in the right biliary system proximal to the confluence, along with choledocholithiasis. Endoscopic retrograde cholangiopancreatography and common bile duct clearance were done; however, the patient underwent hepatic sectionectomy as a curative procedure. ABCB4 mutation was detected on DNA analysis and hence aided in making the diagnosis of low phospholipid-associated cholelithiasis. Additional imaging studies are warranted in doubtful cases. Difficult accessibility of the calculi may often limit endoscopic therapeutic options and pave the way for surgical interventions. As there is an increased risk of cholangiocarcinoma in these patients, regular follow-up is essential.
Keywords: ABCB4; gallstones; hepatolithiasis; intrahepatic calculi; magnetic resonance cholangiopancreatography